IMPLEMENTATION OF FREE EDUCATION IN RELATION TO SCHOOL MANAGEMENT AT PUBLIC JUNIOR HIGH SCHOOL 5 DENPASAR - Gede Putra Wijaya, I Made (E-Journal of Cultural Studies, 2013)
The present study was intended to understand and deconstruct the ideology and reality hidden in the implementation of free education especially at Public Junior High School (SMPN) 5 Denpasar. The ideology appeared from the capitalistic world where a decision was made by the government to make education free of charge. Further, such a decision was issued when the general elections for the legislators and president were about to be held in 2009. It was this which inspired the writer to deconstruct the ideology and reality hidden in the decision made by the government to make education free of charge. The approach of cultural studies was employed in the present study. The informants were chosen using snow-ball technique, meaning that the longer the informants were determined, the more were involved. The data were collected using three techniques; they were observation, in-depth interview, and documentary study. Then the data collected were descriptively and qualitatively analyzed. The result of the study showed that there was an ideology hidden in the policy made to make education free, that is, an attempt to attract people in such a way that they, through the elections for legislators and president held in 2009, would support those who were in the political superstructure. Consequently, their state of being established could be maintained. In addition, such a policy was made as part of the politics of image as an attempt to maintain the status quo.